Implementasi Sistem informasi Pengelolaan Donasi pada Yayasan Ilmu Tanpa Batas berbasis Odoo - Arafah, Nurfauziah; Rusmanto, Rusmanto (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
Ungu Peduli Campus Alumni (AKU Peduli) is a foundation that works in the social and humanitarian fields. AKU Peduli develops its activities through community fundraising and social fund management for business actors. AKU Peduli currently utilizes the most crucial online application, the website. This study aims to determine the process of needs analysis and design of a donation information system to produce system specifications and features required by users, as well as to assess the process of evaluating the results of a donation information system, starting from system installation and data entry to testing. This research was conducted using descriptive qualitative research methods, and the primary data source came from interviews. The research stages start from preliminary studies, needs analysis, system design, implementation, and drawing conclusions and suggestions. The result of this research is that the AKU Peduli website that has been repaired can become a more informative and functional website, making it easier for users to access it. Based on the results of tests that the owner of AKU Peduli has carried out, he considers that the website built has met the criteria for functional requirements. However, some have yet to be realized on this website. The reason is that the AKU Peduli organization has yet to collaborate with several fintech companies. Then the limitations of the website builder features on Odoo are also the reason for the need for more development of the AKU Peduli website.